Analisis Strategi Bauran Pemasaran Hijau Terhadap Eskalasi Volume Penjualan Produk Kreatif Upcycling - Putri Dahlia Sihombing; Alfi Prastia Putri; Bunga Ananda Lestari Sianipar; Vina Marsyah Lyrani; Rosintan Sipayung (Journal of Innovative and Creativity, 2026)
This quantitative study examines the influence of green marketing mix strategies, specifically pricing and product quality, on sales volume escalation of creative upcycling products particularly keychains in Indonesia. As the global economy transitions toward a circular framework, understanding consumer purchasing behavior regarding waste-based goods becomes essential for achieving sustainable business development. Employing a quantitative research methodology, this study analyzed a sample of 42 respondents through simple random sampling. Data collection via Likert-scale questionnaires was analyzed using multiple linear regression with SPSS 26 software. Findings demonstrate that price exerts a dominant, positive, and statistically significant influence on sales growth (p < 0.05), explaining approximately 67.5% of variance through standardized coefficient analysis. Conversely, product quality demonstrates no significant partial impact (p = 0.261), suggesting that consumers prioritize affordability over technical material specifications for low-involvement upcycled items. Simultaneously, the integrated marketing mix of pricing and quality explains 69.8% (R² = 0.698) of sales variance. These results indicate that price functions as critical perceived behavioral control, where ethical environmental preferences remain secondary to economic pragmatism. The study concludes that for sustainable growth in upcycling MSMEs, operational cost efficiency must be prioritized to maintain competitive pricing while leveraging aesthetic innovation and transparent storytelling to mitigate quality skepticism and build consumer trust in circular economy products.